KESEJAHTERAAN PSIKOLOGIS BERBASIS AL-QUR’AN SEBAGAI IMUNITAS PSIKIS-SPIRITUAL - Nurbaiti; Muhammad Hariyadi; Aas Siti Sholichah; Desy Ayu Ningrum (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2021)
This article describes the psychological well-being based on the Al-Qur'an as psychic-spiritual immunity, especially in the face of the Covid-19 pandemic. Psychological well-being is one of the factors of a person's happiness and health in life. Psychological welfare based on or based on the Al-Qur'an is expected to be able to increase immunity, especially for Muslims in the face of the Covid-19 pandemic. This paper supports Laura A. King's opinion regarding the factors of psychological well-being and relates it to the verses of the Al- Qur'an. This paper also produces several responses from the Al-Qur'an on psychological well-being